The value of breast MRI in high‐risk patients with newly diagnosed breast cancer to exclude invasive disease in the contralateral prophylactic mastectomy: Is there a role to choose wisely patients for sentinel node biopsy?. (18th March 2016) - Freitas, Vivianne; Crystal, Pavel; Kulkarni, Supriya R.; Ghai, Sandeep; Bukhanov, Karina; Escallon, Jaime; Scaranelo, Anabel M.
Abstract: The aim of this study was to evaluate the presence of clinically and mammographically occult disease using breast MRI in a cohort of cancer patients undergoing contralateral prophylactic mastectomy (CPM) and the utmost indication of axillary assessment (sentinel node biopsy (SLNB)) for this side. A retrospective review of patients with unilateral invasive breast cancer or ductal carcinoma in situ (DCIS) from institutional MRI registry data (2004–2010) was conducted. Characteristics of patients undergoing CPM with breast MRI obtained less than 6 month before surgery were evaluated. A total of 2322 consecutive patients diagnosed with DCIS or stage I to III infiltrating breast cancer underwent preoperative breast MRI. Of these, 1376 patients (59.2%) had contralateral clinical breast exam and mammography without abnormalities; and 116 patients (4.9%) underwent CPM (28 excluded patients had breast MRI more than 6 months before CPM). The mean age of the 88 patients was 49 years (range 28–76 years). Two (2.3%) DCIS identified on surgical pathology specimen were not depicted by MRI and the 5 mm T1N0 invasive cancer (1.1%) was identified on MRI. Preoperative MRI showed 95% accuracy to demonstrate absence of occult disease with negative predicted value (NPV) of 98% (95% CI: 91.64–99.64%). Occult disease was present in 3.4% of CPM. MRI accurately identified the case of invasive cancer in this cohort. The high negative predictive value suggests that MRI can be used to select patients without consideration of SLNB for the contralateral side. Abstract : The greatest strength of our study certainly is to confirm the highest MRI‐negative predictive value for invasive cancers (IC) in this cohort that was of 100%. The clinical impact is relevant when obtained by a noninvasive preoperative method as the sentinel node biopsy (SLNB) is the standard procedure in patient with invasive disease.